AN EVALUATION OF FACTORS THAT CONTRIBUTETO ENGLISH SECOND LANGUAGE ACQUISITION IN THE UPPER PRIMARY PHASE OF AN URBAN SCHOOL IN NAMIBIA: A CASE STUDY - Mweneni Hautemo, Ms. Aletta; Homateni Julius, Mr. Lukas (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
Majority of Namibian learners are not native speakers of English, that is, they barely speak English in their homes. Yet English is the medium of instruction in many Namibian schools. Many Namibian learners therefore face the double challenge of acquiring the English as the language of teaching and learning (Medium of Instruction) and at the same time developing the appropriate reading and writing proficiency needed to meet the requirements of the curriculum. This situation has created numerous teaching and learning problems which ultimately contribute to poor literacy levels among many Namibian learners.This paper focuses on language acquisition and literacy. It explores factors that contributes to effective English language acquisition as well as investigate and evaluate how the school context supports English language acquisition of the Upper Primary learners at an urban school in Namibia. Since the study targeted young learners, it has covered their reading skills, reading tools and resources such as the library and classroom which provides a rich learning environment. A qualitative interpretive approach was used to explore the factors that contribute to effective learners English second language acquisition. The theoretical framework was informed by Krashens conception of acquisition (1981; 1982). Data collection methods consisted of questionnaires and interviews were used. The findings indicated that the provision of well-structured classroom activities containing comprehensible input structures a bit beyond the learners current level and a low affective filter to allow them to acquire the second language easily. Moreover, error-based activities help learners to test hypothesis, revise and modify them and in the process develop good language awareness skills that help them to acquire and learn the language consciously. This paper suggests that a good supporting environment for reading, which is scaffold by enough assistance by the teachers and peers helps learners develop good language acquisition and learning skills.